Використання технології комп’ютерного зору для системи розумного догляду за шкірою - Пашаєва, С. М. (ХНУРЕ, 2023)
The given work is devoted to the research of computer vision technologies and existing methods of object recognition in the image in order to solve the problem of identifying facial skin problems. The existing methods were analyzed and convolutional neural networks were chosen for further research. During the research, the most effective values for the number and size of filters, the number of convolutional, fully connected layers, epochs, etc. were selected. As a result, skin care software was developed, which simplifies and accelerates processes such as diagnosing skin defects and daily skin care with the help of the used technologies